Pengaruh moderasi komitmen keagamaan terhadap pengaruh atribut islami pada kepuasan pelanggan (Studi empiris pelanggan bank BMT beringharjo) - Punang Amaripuja; Dina Assyifa Rahmah (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2026)
This research aims to analyze the influence of religious commitment as a moderating variable on the influence of Islamic attributes in the context of sharia banking on customer satisfaction. The research was conducted by distributing questionnaires to 158 Bank BMT Beringharjo customer respondents as research samples. This research use a quantitative approach moderated regression analysis is used as an analytical tool to test research hypotheses. This study found that the embedding of Islamic attributes in BMT Bank services was positively correlated customer satisfaction. In addition, it was found that the moderating effect of the religious commitment variable is significant on two Islamic attributes, namely, Physical Islamic Attributes and Non-Physical Islamic Attributes. This article provides an understanding of how Islamic attributes influence satisfaction and the role of religious commitment as a moderator. This research was conducted with only one sample taken object of Bank BMT Beringharjo in Yogyakarta. So generalizations need to be done with caution. This paper includes implications for service strategy in the sector service industry, especially sharia banking, including the importance of service strategies based on customer experience, moderation between compliance with Islamic law and customer comfort as well as customization of services based on customers preference